Dysphagia is associated with presynaptic dopaminergic dysfunction and greater non-motor symptom burden in early drug-naïve Parkinson's patients. - Sotirios Polychronis; Georgios Dervenoulas; Tayyabah Yousaf; Flavia Niccolini; Gennaro Pagano; Marios Politis (PLoS ONE, 2019)
Background The underlying pathophysiology of dysphagia is multifactorial and evidence clarifying the precise mechanisms are scarce. Dysfunction in dopamine-related and non-dopamine-related pathways, changes in cortical networks related with swallowing and peripheral mechanisms have been implicated in the pathogenesis of dysphagia. We aimed at investigating whether dysphagia is associated with presynaptic dopaminergic deficits, faster motor symptom progression and cognitive decline in a population of early drug-naïve patients with Parkinson's disease. Methods By exploring the database of Parkinson's Progression Markers Initiative we identified forty-nine early drug-naïve Parkinson's disease patients with dysphagia. Dysphagia was identified with SCOPA-AUT question 1 (answer regularly) and was assessed with MDS-UPDRS Part-II, Item 2.3 (Chewing and Swallowing). We compared Parkinson's disease patients with dysphagia to Parkinson's disease patients without dysphagia, and investigated differences in striatal [123I]FP-CIT single photon emission computed tomography levels. Using Cox proportional hazards analyses, we also evaluated whether dysphagia can predict motor deterioration and cognitive dysfunction. Results Parkinson's disease patients with dysphagia, harbored a greater deterioration regarding motor and non-motor symptoms and decreased [123I]FP-CIT binding when compared with patients without dysphagia. Higher burden of dysphagia (MDS-UPDRS-II, item 2.3) was correlated with lower [123I]FP-CIT uptakes within the striatum (rs = -0.157; P = 0.002) and the caudate (rs = -0.156; P = 0.002). The presence of dysphagia was not a predictor of motor progression (Hazard ratio [HR]: 1.143, 95% confidence interval [CI]: 0.848-1.541; P = 0.379) or cognitive decline (HR: 1.294, 95% CI: 0.616-2.719; P = 0.496). Conclusions Dysphagia is associated with decreased presynaptic dopaminergic integrity within caudate and greater motor and non-motor symptoms burden in early drug-naïve PD.